Comparison of growth, morphometric and meristic parameters of hybrids produced by crossing between Beluga (Huso huso) and Persian Sturgeon (Acipenser persicus) - Pourkazemi, M.; Mohseni, M.; Nurozfashkhami, M.R.; Taheri, S.A.; Chakmehdoz, F.; Baradaran Noviri, S.; Yarmohamadi, M.; Hassanzadeh, M.; Halajian, A.; Kazemi, R.; Bahmani, M. (2006)
Reciprocal crosses betvveen Beluga and Persian Sturgeon in four treatments and three replications were conducted and reproduction metrics including number of eggs per gram, percentage of fertilization, and survival rate were assessed. Also, we measured 32 morphomeiric and meristic attributes of brood stocks, hybrids and controls. To compare the growth rate of hybrids and controls, fingerlings were grown for 18 months in 2000 liter fiberglass tanks and fed by pellets. During rearing period, 17 samples were taken in 15-30 days interval and total weight and length of the specimens were measured. Average weight and length, standard deviation, analysis of variance, Duncan test and Heterosis were calculated. We found a significant difference (13<0.003) between numbers of eggs of Beluga (controls) in comparison with hybrid (6Beluga x Persian sturgeon) and between Persian sturgeon's eggs with hybrids (Y Beluga x dPersian sturgeon). However, no significant differences were found (1)?0.001) between controls and treatments in terms of fertilization rate (in stage 4 and 35), number and mortality rate of larvae during active feeding and final stages. Hybrid and control fingerlings showed different growth performances. After an 18 months rearing period, the highest growth was found in Beluga (975±10 grams), with hybrid of female i al Beluga and male Persian sturgeon coming next (840±143 grams), hybrid of male Beluga with female Persian sturgeon being the third (681.152$1 grams). The slowest growth rate was seen in control Persian sturgeon with an average growth of 535.15±131 grams. Daily growth rate of hybrids produced from crossing of female Beluga with male Persian sturgeon was higher than control Beluga during second and third rearing period each taking six months. We observed significant differences (p<0.05) in 31 morphometric and meristic parameters from a total of 32 attributes. The percentage of heterosis was variable, being -73.76 in early growth period and 0.79 at the final rearing stage with an average ...